2022
DOI: 10.1007/s10459-022-10128-4
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of interprofessional education: a scoping review

Abstract: Introduction Implementation of interprofessional education (IPE) is recognised as challenging, and well-designed programs can have differing levels of success depending on implementation quality. The aim of this review was to summarise the evidence for implementation of IPE, and identify challenges and key lessons to guide faculty in IPE implementation. Methods Five stage scoping review of methodological characteristics, implementation components, challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 50 publications
0
24
0
3
Order By: Relevance
“…This is consistent with review findings. Reeves et al (2011) reported that IPE education was largely atheoretical, with only six out of 54 included papers reporting learning theories, and that these were minimally applied in the development of the learning activities (Bogossian et al, 2022).…”
Section: Learning Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with review findings. Reeves et al (2011) reported that IPE education was largely atheoretical, with only six out of 54 included papers reporting learning theories, and that these were minimally applied in the development of the learning activities (Bogossian et al, 2022).…”
Section: Learning Constructsmentioning
confidence: 99%
“…Nonetheless, evidence-based design should be aspired to. Having previously addressed evidence in implementation of IPE (Bogossian et al, 2022) and to limit the size of this review and make recommendations useful for designers, there was a need to identify components of design discrete from those of implementation. This necessitated some arbitrary decisions.…”
Section: Strengths and Potential Limitationsmentioning
confidence: 99%
“…The de nition of Interprofessional Education (IPE) (Bogossian et al, 2022; World Health Organization [WHO], 2010) is now well known to the medical education community. In the global space, IPE is known for improving health education, quality of healthcare, and healthcare outcomes, and is ourishing in High-Income Countries (HIC), but not in Low and Middle-Income Countries (LMIC) (Anderson, 2017;Frenk et al, 2010;Sunguya et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Na esfera micro (ensino) é necessário o estímulo à socialização, diminuir percepções errôneas e esteriótipos negativos, estrutura física, desenvolvimento do corpo docente e disponibilidade dos estudantes para a EIP. Na esfera meso (institucional), são essenciais lideranças fortes e comprometidas, recursos financeiros e estrutura física e, na esfera macro (sistêmico), um sistema educacional e estruturas institucionais, políticas governamentais de saúde promotoras da EIP(BOGOSSIAN et al, 2022).1.1.à integração interprofissional e recursos para o desenvolvimento da aproximação docente/assistência(BARR, 2015; PAIVA et al, 2008;PEDUZZI et al, 2013).Iniciativas relevantes ocorreram nas décadas seguintes, que tinham como alvo reorganizar a formação em saúde em direção aos construtos conceituais e metodológicos da EIP.No início da década de 1990, houve uma importante iniciativa para alterar a formação médica, nas universidades de Londrina, Marília, Botucatu, Brasília, Salvador e Natal, do programa UNI -Uma Nova Iniciativa na Educação dos Profissionais do Setor de Saúde, patrocinada pela Fundação Kellogg. O programa propunha uma mudança no modelo de ensino, a partir das críticas ao modelo flexneriano, incorporando a multiprofissionalidade, a interdisciplinaridade e a integração ensino/serviço (BARR, 2015;FREIRE FILHO et al, 2019)…”
unclassified
“…E, finalmente, no plano macro ( apoio político do governo, suporte de políticas indutoras e propostas de sustentabilidade), os coordenadores citam a necessidade de reconhecimento das instituições de ensino e de saúde sobre a importância da EIP e melhoria por parte dos gestores da articulação ensino-serviço. Estes obstáculos também são descritos em revisões de literatura nacional e internacional, como desafios para a implementação da EIP(BOGOSSIAN et al, 2022; DE GOES; CIRINO, 2022).Apesar das dificuldades relatadas, é necessário evidenciar que existem iniciativas brasileiras demonstrando resultados positivos na implementação da EIP. Dentre elas, a disciplina eletiva de Práticas Integradas em Saúde ,com 15 cursos de graduação da área da saúde, da Universidade Federal do Rio Grande do Sul (ELY; TOASSI, 2018); a disciplina curricular de Interação Universidade-serviço-comunidade (Iusc), na Faculdade de Medicina de Botucatu para os cursos de Enfermagem e Medicina (SANTOS; SIMONETTI; CYRINO, 2018); formação interprofissional na UNIFESPcampus Baixada Santista, com um desenho curricular com eixos comum para os cursos de Nutrição, Psicologia, Fisioterapia, Terapia Ocupacional, Educação Física e Serviço Social ( BATISTA et al, 2018); disciplinas curriculares Atenção em Saúde I e II, na Universidade Estadual de Maringá, para estudantes da área da saúde incluindo os estudantes de Medicina (MIGUEL et al, 2018 ); VER-SUS em Sobral, no Ceará, com estudantes de 13 cursos de graduação (AMARAL et al, 2018); além das experiências EIP em projetos de extensão, nos programa do Pet-Saúde e Pró-Saúde em diversas IES.Essas iniciativas demonstram que, algumas universidades já avançaram na implementação da EIP.…”
unclassified